2023
DOI: 10.3389/fpubh.2023.1238738
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to COVID-19 vaccine uptake: classification and the role of Health Literacy and Media Literacy

Soheila Ranjbaran,
Khalil Maleki Chollou,
Sara Pourrazavi
et al.

Abstract: BackgroundVaccination is one of the most influential and cost-effective health interventions for preventing and reducing COVID-19 diseases. Unfortunately, the majority of the world's population is deprived of vaccination. Health Literacy (HL) and Media Literacy (ML) are essential to the COVID-19 vaccination. The present study investigates the barriers to COVID-19 vaccine uptake, focusing on classification and the roles of HL and ML.MethodsA cross-sectional study was conducted among people 18–65 years old in Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…However, there were different results from previous studies in the association between the gender variable and IDSHL. [8,26] The difference may be related to the diversity of culture and social background of regions or countries and different goal groups in studies. A study was conducted in Khalkhal, which demonstrated that low levels of education and family income hindered achieving e-health literacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there were different results from previous studies in the association between the gender variable and IDSHL. [8,26] The difference may be related to the diversity of culture and social background of regions or countries and different goal groups in studies. A study was conducted in Khalkhal, which demonstrated that low levels of education and family income hindered achieving e-health literacy.…”
Section: Discussionmentioning
confidence: 99%
“…[5] Recently, more and more studies have emphasized the importance of health literacy in preventing the COVID-19 pandemic, but there are very few studies regarding the prevention and control of infectious disease. [6][7][8] Infectious disease-specific health literacy (IDSHL) reflects residents' ability to maintain and promote their own health by comprehending and applying relevant knowledge of the occurrence, prevention, and treatment of infectious diseases. [9,10] IDSHL was closely related to reducing the symptoms of relevant infectious diseases among residents.…”
Section: The Authors Have No Conflicts Of Interest To Disclosementioning
confidence: 99%
“…The impacts of the COVID-19 pandemic include disruptions in people’s daily lives and social connections and a reduction in the experience of the sense of belonging ( Allen and Furlong, 2021 ; Lim et al, 2021 ). In addition, the COVID-19 pandemic has had significant psychological effects on different levels of society, such as high levels of anxiety, depression, stress, fear, fear of COVID-19 vaccine uptake, boredom, loneliness, uncertainty, post-traumatic stress symptoms, confusion, anger, and stigma, which are psychological distress signs in patients ( Brooks et al, 2020 ; Duan and Zhu, 2020 ; Ranjbaran et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%